PKM ikan mas (Cyprinus) pindang manis di Kecamatan Bantimurung Kabupaten Maros - Nur Eny P; Hajrah Hamzah; St Fauziah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This program aims to provide solutions and assistance in the utilization and processing of natural resources (Cyprinus) which are potential to have a selling value in Bantimurung, Maros. Assistance is given to increase knowledge and skills in increasing the durability or long- lasting that it can increase the selling price and can be used as an alternative source of new employment opportunities for community members, especially for farmers housewives and girls who drop out of school. The activities carried out were giving training with training materials, including: 1) processing of raw material for into sweet fish products processed by home industries and 2) counseling of product marketing, and the packaging process so that quality products are produced and able to compete. The implementation model of this activity was carried out directly (face-to-face) through training and demonstrations as was the case with the dialogue between the implementing team and activity participants, namely the Mawar Farmers Group and the Mekar Farmers Group in Bantimurung. The results of this programe, Mawar and Mekar Farmers Group leads to the mastery of knowledge and skills so that they can run continuously and can improve the economy of their members.